Penerapan Metode Teams Games Tournament Berbantuan Uno Stacko Dalam Meningkatkan Motivasi Belajar Bahasa Jawa - Usman Hanafi; Tjitrawati; Ucik Fuadhiyah (Piwulang Jurnal Pendidikan Bahasa Jawa, 2024)
Currently, the Javanese language lesson is considered difficult due to the many terms such as language varieties, causing students to feel apprehensive before the lesson. This serves as the basis for this classroom action research, which aims to enhance students' learning motivation in the Javanese language subject by applying the Teams Games Tournament learning method. (TGT). This classroom action research consists of two cycles. Each cycle includes planning, action, observation, and reflection. This research collected data from 22 students in class VII E at SMPN 24 Semarang. The data collection technique for this research uses a student learning motivation observation sheet. Meanwhile, the data analysis technique for this research utilized Excel to process the learning motivation questionnaire data. The research results show an increase in students' learning motivation by 35%, from 55% in cycle I, categorized as having sufficient improvement, to 90% in cycle II, categorized as very good. Thus, the application of the Teams Games Tournament (TGT) learning method assisted by Uno Stacko in increasing motivation to learn Javanese is considered effective and successful. The implication of this research is that after participating in Javanese language learning on the Ramayana puppet story material using the Teams Games Tournament (TGT) method assisted by uno stacko, the students became more active and enthusiastic in their learning.